Analisis Strategi Komunikasi Pemasaran Maxim Dalam Meningkatkan Competitive Advantage Di Kota Bengkulu - Riska Indah Salpitri; Sapta Sari; Indria Indria (Universitas Dehasen Bengkulu, 2023)
This research purpose is to find out communication strategy which used by Maxim company in increasing Competitive Advantage in Bengkulu City. This research used theory from Saban Elchdar (2013) in Sudaryono (2016:274) which involves some components such as competitive pricing, good quality, product innovation and time to market. This research is qualitative research with case study research because the researcher want to observe the information about what can be learned or pulled from related case. Data are collected by using direct observation by doing deep interview and documentation. The result of this research shows that competitive pricing, Maxim has decided basic pricing from all features so the users of Maxim application satisfied with cheap price compared with competitor. The quality of Maxim product keeps developing by increasing the comfort feeling from the users or drivers. Product innovation shows that Maxim has launched some product innovation which can be used to support and help the application user carrying their daily needs. Time to Market in conducting of promotion strategy has run very well online and offline.